2019
DOI: 10.1186/s13578-019-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β in fibrosis by acting as a conductor for contractile properties of myofibroblasts

Abstract: Myofibroblasts are non-muscle contractile cells that play a key physiologically role in organs such as the stem villi of the human placenta during physiological pregnancy. They are able to contract and relax in response to changes in the volume of the intervillous chamber. Myofibroblasts have also been observed in several diseases and are involved in wound healing and the fibrotic processes affecting several organs, such as the liver, lungs, kidneys and heart. During the fibrotic process, tissue retraction rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 161 publications
(195 reference statements)
2
90
0
1
Order By: Relevance
“…A recognized molecular driver of fibrosis is the TGFβ signalling pathway. TGFβ drives the conversion of fibroblasts to myofibroblasts to induce the excessive deposition of collagen and inappropriate ECM during fibrosis, recently reviewed in [127]. Generic molecular markers for myofibroblasts are similar to markers for smooth muscle cells, such as Acta2 (smooth muscle actin), whose expression is regulated by TGFβ signalling [127].…”
Section: Egr1 Is a Fibrotic Factormentioning
confidence: 99%
See 1 more Smart Citation
“…A recognized molecular driver of fibrosis is the TGFβ signalling pathway. TGFβ drives the conversion of fibroblasts to myofibroblasts to induce the excessive deposition of collagen and inappropriate ECM during fibrosis, recently reviewed in [127]. Generic molecular markers for myofibroblasts are similar to markers for smooth muscle cells, such as Acta2 (smooth muscle actin), whose expression is regulated by TGFβ signalling [127].…”
Section: Egr1 Is a Fibrotic Factormentioning
confidence: 99%
“…TGFβ drives the conversion of fibroblasts to myofibroblasts to induce the excessive deposition of collagen and inappropriate ECM during fibrosis, recently reviewed in [127]. Generic molecular markers for myofibroblasts are similar to markers for smooth muscle cells, such as Acta2 (smooth muscle actin), whose expression is regulated by TGFβ signalling [127]. Although myofibroblasts and TGFβ are recognized to be the respective cellular and molecular hallmarks of fibrosis, there is no comprehensive understanding of the cellular and molecular mechanisms underlying fibrosis.…”
Section: Egr1 Is a Fibrotic Factormentioning
confidence: 99%
“…TGF-βs are involved in all multicellular organisms and maintain tissue homeostasis through growth regulation, cell migration, differentiation, epithelial-mesenchymal transition, extracellular matrix remodeling, and immune reactions. However, aberrant overproduction of TGF-β ligands has been identi ed in diseases such as cancer, brosis, and in ammation where hyperactive TGF-β drives disease progression by modulating cell growth, migration, or various phenotypes [27][28][29]. Our results showed that TGF-β was aberrantly expressed following joint immobilization, promoting an in ammatory reaction.…”
Section: Discussionmentioning
confidence: 69%
“…TGF-β and other inducers have been reported to trigger differentiation of dermal fibroblast to myofibroblast during scar formation [61,62]. TGF-β1-induced myofibroblast differentiation through the Smad2/3 signaling pathway increases Hsp47 expression levels [63].…”
Section: Resultsmentioning
confidence: 99%